Letramento digital e orientações educacionais: leitura e escrita digital no ensino médio - Araujo, Elaine Vasquez Ferreira de (2019)
This thesis is part of the research interest Speeches, Social Controls and Resignations of the Doctorate Degree in Humanities, Cultures and Arts of the University of Grande Rio. The general objective of this research is to analyze the historical trajectory of the digital literacy approach in the educational documents produced after LDB/96 (Law of Guidelines and Bases of Education), which base High School and Higher Education. The research is qualitative approach, will be bibliographical part and documentary part. This work is organized in three stages: firstly, a dialogue with literature, aiming to collaborate in the elaboration of a script for the reading and analysis of documents and aiming to answer the question: "What is the role of digital literacy in the formation of the high school student in the information society as a form of development for citizenship and preparation for the job market? ". In the second stage of the research, it concerned the selection and reading of the documents and legislation that guide the educational of High School and the definition of criteria for the analysis of these documents, in order to answer the question "What is the trajectory of the digital literacy in documents that base educational of the High School and in the initial formation of the teacher in Higher Education? ". And the third stage, that aimed at analyzing the historical trajectory of the digital literacy in the educational documents, answered the following questions: "What are the possible relations between the discourses analyzed in the educational guidelines and the contexts of the production of these discourses?" and "What are the possible connections between what the Federal Government proposes for the development of digital literacy in documents that guide the High School and in documents that support the initial formation of the teacher of this segment, in Higher Education? ". In this way, it is possible to observe the role of digital language and digital literacy today for society and the role of educational orientations - organized by the Ministry of Education (MEC) - in the social inclusion of the student, collaborating for the development of skills essential for the exercise of citizenship, means to progress in higher education and in the job market. The results indicated that there are several educational documents that already have discussions about the social practices mediated by the TDICs and the need to develop competences for participation in the digital environment. Observing the historical trajectory of the digital literacy approach in educational documents, it was observed that, shortly after the implementation of LDB in 1996, the educational documents talked about the impacts of technological advances in society and the TDICs as a didactic resource. After 2002, when the Internet becomes more popular among Brazilians, the characteristics of the texts circulating on the Internet become part of some educational documents, even if discreetly. After 2009, there is a growing number of educational documents talking about questions about the characteristics of the language and the texts that circulate on the Internet. In this context, it was found that the publication of some educational documents investigated goes along with the popularization of digital technologies in the country. However, it was observed that there is a certain disharmony between the educational documents focused on the teaching of Portuguese Language in High School and the educational documents aimed at the initial formation of teachers. It is clear that the documents that guide Portuguese Language Teaching in High School are always one step ahead of the documents that guide the teacher training in this segment.